The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.4028/www.scientific.net/kem.777.262
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Activated Carbon-Based Catalyst from Candlenut Shell Impregnated with KOH for Biodiesel Production

Abstract: Candlenut shell is an agricultural waste which can be processed into low-cost active carbon. Activated carbon cannot be used directly as a heterogeneous catalyst in transesterification of biodiesel because of its low alkalinity, thus treatment is required. In this study, the carbonization of candlenut shells was conducted at 500°C for 4 h. The activated carbon obtained was modified by impregnation with potassium hydroxide (KOH) solution. KOH concentration used was 50g/150 ml aqua des and impregnation time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…The powder has irregular shape, uneven, and nonporous surface. These phenomena is also reported by other researchers [7,18,19]. This situation indicates that the powder has small surface area.…”
Section: Iii1 Preliminary Analysis Of MMsupporting
confidence: 86%
“…The powder has irregular shape, uneven, and nonporous surface. These phenomena is also reported by other researchers [7,18,19]. This situation indicates that the powder has small surface area.…”
Section: Iii1 Preliminary Analysis Of MMsupporting
confidence: 86%
“…A mixture with different ratios of Ag on ZnO were prepared, where 10 wt% ZnO@Ag was found to be the most active catalyst producing 96% FAME under the optimum reaction conditions. In the recent past, Taslim et al 129 also demonstrated the efficacy of low-cost AC-based catalysts developed from candlenut shells (an agricultural waste) through the impregnation of KOH for biodiesel production from WCO. The results obtained have shown a yield of biodiesel up to 96.65% using the optimized reaction conditions.…”
Section: Base Catalystsmentioning
confidence: 99%
“…% ZnO@Ag was found to be the most active catalyst producing 96 % FAME under optimum reaction conditions. In the recent past, Taslim et al 129 also demonstrated the efficacy of low-cost AC-based catalyst developed from candlenut shell (an agricultural waste)…”
Section: Supported Catalystmentioning
confidence: 99%